Porous Nanocrystalline Silicon Supported Bimetallic Pd-Au Catalysts: Preparation, Characterization, and Direct Hydrogen Peroxide Synthesis - Potemkin, Dmitriy I.; Maslov, Dmitry K.; Loponov, Konstantin; Snytnikov, Pavel V.; Shubin, Yuri V.; Plyusnin, Pavel E.; Svintsitskiy, Dmitry A.; Sobyanin, Vladimir A.; Lapkin, Alexei A. (Frontiers in Chemistry, 2018)
Bimetallic Pd-Au catalysts were prepared on the porous nanocrystalline silicon (PSi) for the first time. The catalysts were tested in the reaction of direct hydrogen peroxide synthesis and characterised by standard structural and chemical techniques. It was shown that the Pd-Au/PSi catalyst prepared from conventional H2[PdCl4] and H[AuCl4] precursors contains monometallic Pd and a range of different Pd-Au alloy nanoparticles over the oxidized PSi surface. The PdAu2/PSi catalyst prepared from the [Pd(NH3)4][AuCl4]2 double complex salt single-source precursor predominantly contains bimetallic Pd-Au alloy nanoparticles. For both catalysts the surface of bimetallic nanoparticles is Pd-enriched and contains palladium in Pd0 and Pd2+ states. Among the catalysts studied, the PdAu2/PSi catalyst was the most active and selective in the direct H2O2 synthesis with H2O2 productivity of 0.5 at selectivity of 50 % and H2O2 concentration of 0.023 M in 0.03 M H2SO4-methanol solution after 5 h on stream at -10 °C and atmospheric pressure. This performance is due to high activity in the H2O2 synthesis reaction and low activities in the undesirable Н2О2 decomposition and hydrogenation reactions. Good performance of the PdAu2/PSi catalyst was associated with the major part of Pd in the catalyst being in the form of the bimetallic Pd-Au nanoparticles. Porous silicon was concluded to be a promising catalytic support for direct hydrogen peroxide synthesis due to its inertness with respect to undesirable side reactions, high thermal stability and conductivity, possibility of safe operation at high temperatures and pressures and a well-established manufacturing process.